Strategic communication as a positioning tool in the case of a marketing career Universidad Estatal de Bolívar - Barreto Bonilla, Jessica; Palacios Shinin, Freddy; Vergara Zurita, Heidy (mktDESCUBRE; Vol 1 No 18 (2021): Eighteenth Edition (July - December), 2021)
The present work analyzes the perception of the communicational strategies proposed by the Marketing career of the State University of Bolívar, which allowed identifying successes, deficiencies and information needs to propose improvements in the strategic communication plan as a tool that stimulates positioning in its publics involved. The research was non-experimental, cross-sectional and descriptive, qualitative-quantitative approach, the inductive, deductive method was used. The data was obtained through online surveys shared with the entire student population of the marketing career of the Bolívar State University. The results show a favorable perception of the communication channels used, they recognized as preferred media the digital platforms Facebook, Instagram, email and WhatsApp groups, however, there is a weak recognition of the corporate image and graphic identity. The following stood out as differentiating attributes: the relevance of the academic program of the career, the qualification of the teaching staff and the social impact on the environment. It was identified that there is no greater presence in traditional media, but it is considered a potential to be taken into account in the development of the communication plan, as well as the realization of integration activities that favor the organizational climate.